Ultrasound and mechanical activation cleaner promote lattice manganese extraction: A combined experimental and modeling study. (1st February 2017) - He, Hongping; Cao, Jianglin; Duan, Ning
Abstract: The potential of ultrasound and mechanical activation (MA) in cutting down the acid amount required for low-grade MnO (manganese ore as received) extraction was extensively investigated in this study. Results showed that MA and heating-up combination could obviously promote Mn dissolution kinetics and thereby achieve higher extraction efficiency under identical H2 SO4 dosage. The positive role of ultrasound was found to be evident in the extraction of MnOA (manganese ore after MA), but negligible for MnO. Such a difference was correlated with the much different physicochemical properties of the liquid/solid systems that ultrasound involved in, as MA was confirmed to induce the dissociation of Mn-containing flocs and SiO2 particles. High potential of ultrasound in weakening the agglomeration of ultra-fine MnOA was also recommended. Semi-empirical Averami equation was found to well model the Mn extraction kinetics, which was much more diffusion controlled after MA based on the modeling. The modeling disclosed high capability of MA in decreasing the activation energy of Mn extraction (from 11.33 to 5.43 kJ/mol), whereas, ultrasound was effective in enhancing mass transfer or promoting pre-exponential factor A. Considering the potential in assisting efficient extraction via a cleaner way, ultrasound and MA combination provides a feasible alternative in mediating the hydrometallurgy of low-grade minerals. Highlights: Mechanical activation (MA) and ultrasound obviously promote the manganese ore extraction. Various manganese ore dissolution kinetics could be well modeled by Averami equation. MA and ultrasound were found to mediate manganese ore dissolution differently. MA and ultrasound combination is promising for cleaner promotion of mineral extraction.